Managing nursing care to puerperae and newborns in primary healthcare - Tamiris Scoz Amorim; Marli Terezinha Stein Backes (Universidade Federal do Ceará, 2020)
Objective: understanding the meaning of managing nursing care for puerperae and newborns in primary healthcare. Methods: qualitative study, based on the theoretical framework of Data-based Theory. Participant observation and semi-structured individual interviews were conducted with eleven primary healthcare nurses. The analytical process involved open, axial, and selective coding/integration. Results: the central phenomenon, Promoting the management of nursing care in primary healthcare, indicates the leadership of nurses when dealing with challenges in the context of care. That suggests actions and interactions to guarantee autonomy and the quality of care, in addition to empowering the parents. Conclusion: the management of care from nurses who participated in the research aims to embrace the mother-child and family particularities since the prenatal, and to promote a singular, multidimensional, continuous, vigilant, and systematized care, which values the subjectivity and the main role of the woman-mother and the care they should have with themselves and the newborn.